2004
DOI: 10.1128/jcm.42.11.5270-5276.2004
|View full text |Cite
|
Sign up to set email alerts
|

Selective Discrimination of Listeria monocytogenes Epidemic Strains by a Mixed-Genome DNA Microarray Compared to Discrimination by Pulsed-Field Gel Electrophoresis, Ribotyping, and Multilocus Sequence Typing

Abstract: Listeria monocytogenes can cause serious illness in humans, and subsequent epidemiological investigation requires molecular characterization to allow the identification of specific isolates. L. monocytogenes is usually characterized by serotyping and is subtyped by using pulsed-field gel electrophoresis (PFGE) or ribotyping. DNA microarrays provide an alternative means to resolve genetic differences among isolates, and unlike PFGE and ribotyping, microarrays can be used to identify specific genes associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 28 publications
1
40
0
5
Order By: Relevance
“…Rapid, discriminatory, and standardized molecular subtyping methods are critical for effective food-borne disease surveillance and outbreak investigations. While automated ribotyping provides superior standardization and speed compared to many other molecular subtyping methods for bacterial isolates (58), not surprisingly and consistent with the findings of a number of previous studies (1,5,24,32,56), two-enzyme PFGE using the standard PulseNet protocol provides significantly higher subtype discrimination than EcoRI ribotyping. While automated ribotyping is thus suitable for population-based studies or subtype characterization of large numbers of isolates (1), the discriminatory power of PFGE clearly is critical for human disease outbreak investigations.…”
Section: Discussionsupporting
confidence: 72%
“…Rapid, discriminatory, and standardized molecular subtyping methods are critical for effective food-borne disease surveillance and outbreak investigations. While automated ribotyping provides superior standardization and speed compared to many other molecular subtyping methods for bacterial isolates (58), not surprisingly and consistent with the findings of a number of previous studies (1,5,24,32,56), two-enzyme PFGE using the standard PulseNet protocol provides significantly higher subtype discrimination than EcoRI ribotyping. While automated ribotyping is thus suitable for population-based studies or subtype characterization of large numbers of isolates (1), the discriminatory power of PFGE clearly is critical for human disease outbreak investigations.…”
Section: Discussionsupporting
confidence: 72%
“…Future experiments will include design and testing of additional probes to improve L. monocytogenes suspension array subtyping resolution, including the addition of phylogeneticdivision-and species-specific probes. Variable regions of the L. monocytogenes genome have already been identified using planar-microarray analysis (1,3,5). This information can be readily used for the design of additional suspension array probes to allow development of a rapid and high-resolution subtyping assay for L. monocytogenes isolates.…”
Section: Resultsmentioning
confidence: 99%
“…The most recent examples of this are multilocus sequence subtyping (12,17) and microarray genomic analysis (1,5,26). Recent studies have shown that a relatively simple genotyping microarray has subtyping resolution comparable to that of pulsed-field gel electrophoresis (AscI and ApaI digestion) and superior to that of multilocus sequence subtyping (six housekeeping genes) and ribotyping (3). L. monocytogenes subtyping using DNA microarrays is also genetically informative because it can identify the genes or alleles that characterize subtypes.…”
mentioning
confidence: 99%
“…Con la clasificación alimentaria expuesta anteriormente, el criterio establecido en los Estados Unidos para aceptar como inocuos los alimentos listos para el consumo en los que puede crecer L. monocytogenes, es de cero tolerancia (10,16,47,48,65,68,69). Europa acepta niveles hasta de 100 unidades formadoras de colonias (UFC) para algunos alimentos que no estén destinados a poblaciones vulnerables (47).…”
Section: Los Centers For Disease Control and Preventionunclassified